2023
DOI: 10.2196/40028
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characterization of Post-COVID-19 Symptoms in Hospitalized COVID-19 Survivors to Recognize Syndemic Connotations in India: Single-Center Prospective Observational Cohort Study

Abstract: Background Long COVID, or post-COVID-19 syndrome, is the persistence of signs and symptoms that develop during or after COVID-19 infection for more than 12 weeks and are not explained by an alternative diagnosis. In spite of health care recouping to prepandemic states, the post-COVID-19 state tends to be less recognized from low- and middle-income country settings and holistic therapeutic protocols do not exist. Owing to the syndemic nature of COVID-19, it is important to characterize post-COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Previous studies, including those conducted in low-and middle-income countries, have established a link between female gender and long COVID ( 12 , 13 , 21 23 ), However, it has not been previously reported that a positive depression screening at day 30 using a validated questionnaire could be a risk factor for diagnosing long COVID at day 90 ( 24 , 25 ). Additionally, few studies have examined depression as a risk factor for COVID-19 or long COVID ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies, including those conducted in low-and middle-income countries, have established a link between female gender and long COVID ( 12 , 13 , 21 23 ), However, it has not been previously reported that a positive depression screening at day 30 using a validated questionnaire could be a risk factor for diagnosing long COVID at day 90 ( 24 , 25 ). Additionally, few studies have examined depression as a risk factor for COVID-19 or long COVID ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 97%
“…In Malaysia, common symptoms observed in both outpatients and inpatients include fatigue, brain fog, depression, anxiety, insomnia, and joint or muscle pain ( 12 ). However, in India, a single-center prospective observational cohort study highlighted fatigue, dyspnea, and weight loss as the predominant symptoms among hospitalized patients ( 13 ). A study in China found that at 6-month follow-up, fatigue or muscle weakness and sleep difficulties were the main symptoms observed in COVID-19 patients who had recovered.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior prospective study involving the same cohort, we observed a 60% prevalence of PCC at the end of six weeks [12]. However, that study did not employ laboratory parameter analysis to investigate predictive risk factors for PCC.…”
Section: Introductionmentioning
confidence: 94%
“…Indivíduos recuperados da COVID-19 podem apresentar sintomas persistentes por um longo período após a infecção aguda, bem como desenvolver novas alterações clínicas associados ao pós-COVID-19. A sintomatologia dessa condição inclui fadiga, artralgia, fraqueza muscular, dispneia, dor torácica, distúrbios do sono, dentre outros (Nalbandian et al, 2021;Malik et al, 2022;Halpin et al, 2021;Besnier et al, 2022, Saboia;.…”
Section: Introductionunclassified